(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Menstruation is the end point of series of events which begin in the cerebral cortex and hypothalamus and ends at the uterus in the hypothalamic pituitary –ovarian uterine axis. Any break in this axis creates Menstrual Problems. PCOS is one such condition associated with abnormal gonadotropic secretion which in turn lead to menstrual irregularity acne and hirsutism- Its prevalence ranging from 2.2% to 26% with age ranging from 18-45 years. In modern science PCOS is managed by down regulating HPO axis using Hormonal Pills which have their own side effects. Therefore complete, comprehensive and holistic approach towards its understanding & treatment is the need of the age. Ayurveda has no direct correlation to PCOS. There are similar condition acc to symptoms are explained under the concept of Pushpaghni, Jathaharini. Here under PCOS w.s.r. to Oligomenorrhoea, interval between menses, duration of flow, amount of flow and other symptoms like pain are considered. The effect of Anjani vati (Trial drug) is compared with Krishna Tila Kalka (Control Drug) in two groups containing 30 patients each.